Effect of mixture proportions on the drying shrinkage and permeation properties of high strength concrete containing class F fly ash - Nath, Pradip; Sarker, Prabir (Springer, 2013)
Sustainability of concrete can be improved by using large volume of fly ash as a replacement of cement and by ensuring improved durability of concrete. Durability of concrete containing large volume of class F fly ash is dependent on the design of mixture proportions. This paper presents an experimental study on the effect of mixture proportions on the drying shrinkage and permeation properties of high strength concrete containing large volume local class F fly ash. Concrete mixtures were designed with and without adjustments in the water to binder ratio (w/b) and the total binder content to take into account the incorporation of fly ash up to 40% of total binder. Concretes, in which the mixture proportions were adjusted for fly ash inclusion achieved equivalent strength of the control concrete and showed enhanced properties of drying shrinkage, sorptivity, water permeability and chloride penetration as compared to the control concrete. The improvement of durability properties was less significant when no adjustments were made to the w/b ratio and total binder content. The results show the necessity of the adjustments in mixture proportions of concrete to achieve improved durability properties when using class F fly ash as a cement replacement.